Analisis Pengangguran dan Kebijakan Pemerintah Terhadap Perekonomian Indonesia - Moch Rifqi Shihabuddin Al Ubaidillah; Muhammad Yasin (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research analyzes the unemployment rate in Indonesia and the impact of government policies on the national economy. Unemployment is a significant economic problem in Indonesia, with various factors influencing it, including population growth, structural economic changes, and technological changes. This study uses secondary data from the Central Statistics Agency (BPS) and various other sources to evaluate unemployment trends in recent decades. The results of the analysis show that the unemployment rate in Indonesia experiences fluctuations which are influenced by global economic conditions, government policies and the dynamics of the domestic labor market. Government policies, such as job training programs, increased infrastructure investment, and support for the MSME (Micro, Small and Medium Enterprises) sector, have played an important role in reducing unemployment. However, challenges such as a mismatch of skills and labor market needs, as well as regional disparities, are still significant obstacles.